2014
DOI: 10.1159/000363279
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Natriuretic Peptides and Incidence of Subtypes of Ischemic Stroke

Abstract: Background and Purpose: Natriuretic peptides predict poor outcomes in cardiovascular disease. However, the knowledge of their relationship to stroke is limited and prospective studies from the general population are few. The purpose of this study was to explore the relationship between N-terminal pro-brain natriuretic peptide (NT-proBNP) and midregional pro-atrial natriuretic peptide (MR-proANP) plasma levels and the risk for ischemic stroke and its subtypes. Methods: NT-proBNP and MR-proANP were measured in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 32 publications
(47 reference statements)
1
23
0
Order By: Relevance
“…7 Largescale prospective cohort studies found that increased natriuretic peptides were significantly associated with increased risks for incident stroke, 3,4 although the mechanism is not clear. Clinical studies reported that natriuretic peptides were increased in patients with stroke and associated with infarct size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Largescale prospective cohort studies found that increased natriuretic peptides were significantly associated with increased risks for incident stroke, 3,4 although the mechanism is not clear. Clinical studies reported that natriuretic peptides were increased in patients with stroke and associated with infarct size.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increased natriuretic peptides were suggested to be risk factors for stroke, although the mechanism is not clear. 3,4 Human corin, a type II transmembrane serine protease highly expressed in the heart, 5,6 played a physiological role in the activation of natriuretic peptides. 7 This indicated a potential role of human corin in stroke.…”
Section: See Related Article P 1755mentioning
confidence: 99%
“…73 NT-proBNP is an independent predictor of cardiovascular events including incident AF in epidemiological and clinical populations, 7477 and NT-proBNP has been associated with subclinical cerebrovascular disease 78 and risk of cardioembolic stroke. 79, 80 NT-proBNP is also associated with increased likelihood of detection of paroxysmal AF in patients with ischemic stroke. 81, 82 …”
Section: Biomarkers Of Atrial Cardiopathymentioning
confidence: 99%
“…A prospective cohort study concluded that people with an elevated MRproANP are at a higher risk to experience a cardio-embolic stroke. The risk of other stroke subtypes is not elevated [51]. MRproANP is a precursor hormone of atrial natriuretic peptide (ANP) which regulates blood pressure [52].…”
Section: Discussionmentioning
confidence: 99%